Uncertainty in atmospheric profiles and its impact on modeled convection development at Nam Co Lake, Tibetan Plateau. Issue 22 (19th November 2013) - Gerken, Tobias; Babel, Wolfgang; Sun, Fanglin; Herzog, Michael; Ma, Yaoming; Foken, Thomas; Graf, Hans‐F.
<x xml:space="preserve">Abstract</x> [1] This work investigates the influence of atmospheric temperature and relative humidity profiles obtained from radio soundings, NCEP‐I and ERA‐Int reanalysis and GFS‐FNL analysis data on the simulated evolution of clouds and convection at Nam Co Lake on the Tibetan Plateau. In addition to differences in moisture, the initial atmospheric profiles exhibit considerable differences in near‐surface temperatures that affect vertical stability. Our analysis is carried out during 2 days in summer 2012 using a 2‐D high‐resolution modeling approach with a fully interactive surface model so that surface fluxes react to changes in cloud cover. Modeled convection for the radio‐sounding profile compares reasonably well with weather observations for the first day, but less well for the second day, when large‐scale synoptic effects, not included in the model, become more important. The choice of vertical profile information leads to strongly differing convection development, translating into modifications of the surface energy balance and of the energy and water cycle for the basin. There are strong differences spanning one order of magnitude in the generated precipitation between the model simulations driven by different vertical profiles. This highlights the importance of correct and high‐resolution vertical profiles for model initialization.